Nature conservation planning approach in the urban epoch - Koyunoglu, Balm; Gulersoy, Nuran Zeren (International Planning History Society Proceedings, 2018)
This study explores the nature conservation planning in the urban context, an emerging issue in the process of striking a balance between natural heritage conservation and urbanization demands, by focusing on two cases: Breda City Plan in the Netherlands and Beykoz Riva Integrated Environmental Protection and Development Plan. Breda City Plan is analyzed as a reflection of a deep-rooted tradition that is sensitive to nature while Riva Beykoz Plan is analyzed as a unique example within Turkey in that regard. These cases see the development of an integrated rainwater management system by the enhancement of existing ecosystems and green urban spaces and by their connection to the adjacent protected natural areas. This study explores whether the recent implementations of nature conservation in Breda and Beykoz Riva meet IUCN guidelines for urban areas. These cases are analyzed with the IUCN Urban Protected Area Guidelines which adopts current concept and methodology of nature conservation planning in urban areas. As a result of their analysis, it is observed that they both meet the guideline criteria.